British economic growth and development - Broadberry, S (University of Oxford, 2022)
British per capita GDP grew at an average annual rate of 0.13 per cent between 1086 and 1700. Although the annual growth rate increased to 0.48 per cent between 1700 and 1870, the period covering the Industrial Revolution, this was still not particularly fast. What mattered for Britain’s catching-up and forging ahead of other economies was its resilience, with few episodes of negative growth. By the late nineteenth century, other countries had begun to emulate Britain’s Industrial Revolution and by the beginning of the twentieth century, the United States had emerged as the new per capita income leader. However, the process by which the United States and Germany overtook Britain owed more to a later structural shift out of agriculture and developments within services than to any change in the comparative productivity position within manufacturing. After 1870, other countries were bound to grow faster than Britain while catching-up, and once Britain had fallen behind, it too could benefit from borrowing technology and institutions from abroad. TFP growth has been an important proximate source of Britain’s rise to GDP per capita leadership and also of Britain’s relative economic decline since 1870. However, the ultimate source of these developments in technology lies in the institutional framework. Britain’s rise to GDP per capita leadership occurred as innovators responded to the factor price combination that they faced within an environment shaped by the Enlightenment. After 1870, British relative decline occurred as barriers to competition arose and slowed the response to technological change.